M20 Pleural service in a large university teaching hospital – 1 year retrospective review. (15th November 2016) - Fawzi, A; Maddekar, N; Khan, S; Bikmalla, S; Iqbal, M; Abi Musa Asa'ari, AKA; Cusay, T; Austin, A; Moore, C; Haris, M
Abstract : Introduction: Over the last decade, there has been a paradigm shift in the management of both pleural effusions and pneumothoraces. Specialty pleural day-case services have been established offering one-stop clinical assessment, imaging and intervention, with a view to early diagnosis, improved patient care and admission avoidance. We wished to evaluate the pleural service at a large university teaching Hospital. Methods: 650 consecutive outpatient episodes presenting to the pleural day-case clinic between January 2015 and January 2016 were reviewed. Patient characteristics, source of referral, diagnosis, interventions and outcomes were evaluated. Results: Total number of patient episodes: 650. 264 new outpatients, 322 outpatient follow-ups, 64 pleural in-reach. Male 403 (62%), Female 247 (38%). Referral Source: GP 151 (58%), acute medicine unit/A&E/other specialties 103 (38%) and external referrals 10 (4%). Pleural Interventions: 27 diagnostic aspirations, 113 therapeutic aspirations, 27 chest drain insertions, 37 indwelling pleural catheters. Indications for referrals: Pneumothorax: 24, 27 parapneumonic/Complicated effusions, 57 known malignancy, 150 unknown effusions, 8 others. Average length of stay (based on the BTS Pleural audit 2014) 1 was 8 days. Admission avoidance: 264 patients × 8 days = 2, 112 bed days saved in 48 weeks. Early discharge assuming 4 days (66 patients × 4 days) = 264 bed days saved. Total bed days saved = 2376 in 48 weeks – Equivalent of 7 bed days per patient. Conclusions: A dedicated pleural service has resulted in improvement in both patient outcomes and experience. The number of unnecessary pleural procedures has reduced. Complicated cases are discussed in Pleural MDT meetings. A recent patient feedback survey conducted over 2 months has shown a highly favourable patient experience of the service itself. The pleural service has allowed the department to recruit to several appropriate NIHR trials. The number of bed days saved is significant, raising the question as to whether a nationwide adoption of pleural services in the majority of trusts, would take some of the strain off of an overburdened NHS. Reference: Hooper CE, Welham SA, Maskell NA. Pleural procedures and patient safety: a national BTS audit of practice. Thorax 2013;70 (2):189–191.